External Debt Origin, Capital Flight and Poverty Reduction in the Franc Zone: Does the Economic Consequences of Sino-African Relationship matter? - Christian-Lambert Nguena (African Governance and Development Institute (AGDI), 2014)
Is China-Africa economic relation instrumental for capital flight and poverty reduction in FZ? Does it matter in the improvement of external debt's impact on GDP per capita and capital flight reduction in particular? This paper extends and assesses the Asongu and Aminkeng (2013) conclusions about Sino-African economic relations in the FZ context.Thus, practically, the intuition is to use a TSLS-IV econometric estimation technique on 14 African countries specific data over the period 1983-2013 to empirically assess if African external debt exclusively from China can be instrumental in the way toward capital flight and poverty reduction in FZ. The construction of a theoretical framework highlighting stylized fact and the review of a recent literature on this issue has been firstly undertaken. The main result allowed the following interpretations: (a) an important part of the traditional external debt contracted with constraint is going back out of the continent as capital flight and; (b) The capital flight contributes to improving the level of poverty in Africa. Overall, we can conclude that the contribution to economic development depends on the origin of loans received and, fostering the economic relations with China could be an excellent alternative for FZ countries. This paper is original since it has tested the Asongu and Aminkeng (2013) assumption in the continent where concerns of low economic development, higher poverty and capital flight are most acute.
Keywords: E61; E62; H11; I32; O10; O19; 330; Sino-African economic relation; Capital flight; External debt origin; pro poor economic growth; Poverty reduction